2009
DOI: 10.3945/jn.108.096354
|View full text |Cite
|
Sign up to set email alerts
|

Iron Is Essential for Neuron Development and Memory Function in Mouse Hippocampus

Abstract: Iron deficiency (ID) is the most prevalent micronutrient deficiency in the world and it affects neurobehavioral outcome. It is unclear whether the effect of dietary ID on the brain is due to the lack of neuronal iron or from other processes occurring in conjunction with ID (e.g. hypoxia due to anemia). We delineated the role of murine Slc11a2 [divalent metal ion transporter-1 (DMT-1)] in hippocampal neuronal iron uptake during development and memory formation. Camk2a gene promoter-driven cre recombinase (Cre) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
199
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(223 citation statements)
references
References 65 publications
18
199
0
6
Order By: Relevance
“…Low serum ferritin is often seen in infants born to severely anemic mothers (23). Hippocampal iron deficiency induced by tissue-specific knockout of Slc11a2 caused defective hippocampal development and spatial memory (24). Collectively, these studies indicate a critical role for maternal iron status and dietary iron in early neural development.…”
mentioning
confidence: 85%
“…Low serum ferritin is often seen in infants born to severely anemic mothers (23). Hippocampal iron deficiency induced by tissue-specific knockout of Slc11a2 caused defective hippocampal development and spatial memory (24). Collectively, these studies indicate a critical role for maternal iron status and dietary iron in early neural development.…”
mentioning
confidence: 85%
“…Iron staining was done using a modified Perls iron staining as described previously (Carlson et al, 2009). Briefly, free floating sections of a P30 control brain and the P30 iron extracted brain were simultaneously incubated for 5 min in 10% potassium ferrocyanide (Sigma Aldrich).…”
Section: Iron Stainingmentioning
confidence: 99%
“…These observations would explain the behavioral findings in human infants that have been associated with ID. [29][30][31] Therefore, taking into account that iron is the world's most common single-nutrient deficiency, it is important to minimize IDA and ID among infants and toddlers, even if an unequivocal relationship between IDA and ID and neurodevelopmental outcomes has yet to be established.…”
Section: Id and Neurodevelopmentmentioning
confidence: 99%
“…3,[23][24][25][26][27][28][29][30][31] Results of a preponderance of studies have demonstrated an association between IDA in infancy and later cognitive deficits. Lozoff et al 3,25 have reported detecting cognitive deficits 1 to 2 decades after the irondeficient insult during infancy.…”
Section: Id and Neurodevelopmentmentioning
confidence: 99%